Black trans feminism - Bey, Marquis (Black outdoors., 2022)
"Marquis Bey offers a meditation on blackness and gender nonnormativity in ways that recalibrate traditional understandings of each, conceiving of black trans feminism as a politics grounded in fugitivity and the subversion of power."--